Supported imidazole as heterogeneous catalyst for the synthesis of cyclic carbonates from epoxides and CO2 - Sankar, Meenakshisundaram; Ajithkumar, Thalasseril G.; Sankar, Gopinathan; Manikandan, Palanichamy (Catalysis Communications, 2015)
Imidazole anchored onto a silica matrix, by means of a propyl linkage, is found to be an effective heterogeneous catalyst for the synthesis of cyclic carbonates from epoxides and CO2 in near quantitative yield. The versatility of this catalyst is demonstrated by using different substrates (epichlorohydrin, propylene oxide, butylene oxide and styrene oxide) for this cycloaddition reaction. These CO2 insertion reactions were typically carried out in the temperature range of 343 to 403 K at 0.6 MPa CO2 pressure under solvent-free conditions. Several spectroscopic methods were used to characterize the catalyst and study the integrity of the fresh and spent catalysts. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Anchored imidazole; CO2 utilization; cyclic carbonates; epoxides